Alternative computer mouse designs: Performance, posture, and subjective evaluations for college students aged 18-25. - Feathers, David J.; Rollings, Kimberly; Hedge, Alan (Work)
BACKGROUND: Students are faced with work demands requiring intense computer use throughout the week, often with cumulative hourly use per day exceeding that of adult workers. Extended daily computer use has been associated with a reported increase of musculoskeletal symptoms for college-aged students. New mouse designs offer alternative movement and postural strategies to potentially mitigate musculoskeletal stress for students. OBJECTIVE: This study investigates the use of alternative computer mouse designs by college-aged students (18-25) through a precision task (point-and-click an on-screen target). Wrist movements, hand posture, and associated subjective user data were collected across innovative mouse designs to understand the physical impact and basic usability issues for this population. PARTICIPANTS: Twenty-one (21) healthy, right handed students (11 female; 10 male) were enrolled in this study. METHODS: Five mouse designs were assessed by investigating hand fit, wrist movements, and subjective accounts of ease of use, perceived control, comfort and aesthetics. Human performance was captured for each mouse design in terms of peak velocity, average movement time, and fastest movement direction using an electrogoniometer as participants performed the ISO 9241 multipoint standard Fitts' task using the Generalized Fitts' Law Model Builder software (GFLMB v.1.1C; [1]) within a zero-error setting (point-and-click task). Hand measurements were taken in both standardized anthropometric positions and adapted hand positions on five alternative mouse designs for a total of seven sets of measurements for each participant. Subjective data was collected through a series of questionnaires that were administered before, during, and after the mouse tasks. RESULTS: Results for human performance, distal upper extremity posture (hand/wrist), and subjective data such as overall preference, ease of use, perceived control, and comfort are given for this population. Wrist extension exceeded 30 degrees for over 50% of the total movement time for 3 out of 5 mouse designs. Postural variations in hand molding of the metacarpophalangeal arch (MCP angle) across mouse design was shown to be related to mouse control and ease of use. Subjective evaluations showed no differences between males and females, and overall preference was correlated to subjective evaluations of comfort, ease of use, perceived control, and, to a lesser extent, product attractiveness. CONCLUSIONS: Individual performance across the alternative mouse designs in this study showed overall faster movement speeds than the `conventional' mouse design, while exhibiting similar wrist posture behavior for extension and ulnar deviation. Wrist extension is a risk factor for musculoskeletal injuries such as carpal tunnel syndrome. The current ergonomic standard calls for wrist extension to be below 30 degrees, and 3 of the 5 mouse designs exceeded this value. Guidance and adherence to proper use techniques for alternative mouse designs for this population is warranted and will help mitigate potential musculoskeletal risks.